Identification of insulator leakage current harmonic content - Ahmad, Hussein (Faculty of Electrical Engineering, 2009)
During service, overhead transmission line insulators lose their functionality due to electrical stresses and environmental conditions causing incessant flow of leakage current (LC) on their surface thereby leading to insulator ageing. Ceramic glass insulators are the oldest type of insulator and constitute a bulk number with some operating for decades and approaching their projected life span. A technique to assess the condition of these ageing insulators on-line or predict their remaining life span has till date not yet been possible. Likewise a study on diagnosis and monitoring of aged ceramic insulators has not been found lacking. In this work, field-aged transmission line glass insulators that have exhibited severe, mild and no degree of ageing with service history ranging from 0 – 40 years were studied. The frequency components of the insulator LC were investigated under different electrical stresses and contamination level. From the study, a strong correlation was observed between the degree/progress of ageing and the 3rd and 5th harmonic ratio of the ageing insulators. In addition, a pattern existed between the LC harmonics distribution of various aged insulators samples. The findings in this research suggest that insulator LC frequency components are good indexes to insulator ageing as well as viable for monitoring and diagnosing ageing insulator for the estimation of insulator lifespan.